2018
DOI: 10.1080/10810730.2018.1436622
|View full text |Cite
|
Sign up to set email alerts
|

The Buddy Benefit: Increasing the Effectiveness of an Employee-Targeted Weight-Loss Program

Abstract: It is well known that significant others (particularly romantic partners) can influence people's weight management efforts. However, what constitutes effective support-and from which type of individual (e.g., romantic partner, family member, friend)-is unclear. Thus, framed by confirmation theory, we assessed the effectiveness and types of communication of a weight-loss "buddy" through reports of 704 individuals enrolled in a 15-week synchronous online weight-loss program. Roughly 54% of participants chose bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Firstly, encouragement can be considered positive reinforcement of desirable behaviour, which may enhance motivation [ 1 ]. If employees perceive their colleagues as endorsing a healthy lifestyle, they may deduce that it is important and be more likely to adopt such behaviours.…”
Section: Explanatory Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, encouragement can be considered positive reinforcement of desirable behaviour, which may enhance motivation [ 1 ]. If employees perceive their colleagues as endorsing a healthy lifestyle, they may deduce that it is important and be more likely to adopt such behaviours.…”
Section: Explanatory Mechanismsmentioning
confidence: 99%
“…Secondly, perceived encouragement could lead to a sense of responsibility towards those offering it. Not only does encouragement reflect what others find important, it also could create a sense of shared effort; employees could get the feeling that they do not want to let their well-meaning colleagues down by making unhealthy choices [ 1 , 15 ]. In this way, colleagues keep one another accountable, for example by motivating the other to go for a lunch walk even when it is raining [ 7 ].…”
Section: Explanatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 34 exploring predictors of adherence to a weight loss programme found that having a buddy (family member or friend) led to an increase in programme adherence from 79.9% to 96.1%. In a study 35 of 704 participants in a 15-week online weight loss programme, 54% of participants chose to use a buddy, and they lost more weight than those who did not have a buddy. The same level of effectiveness was found whether the buddies were romantic or non-romantic.…”
Section: Social Support (Interpersonal Process)mentioning
confidence: 99%
“…• CRF for 36 participants • EQ-5D, ICECAP-A for 35 Data revealed that the HelpMeDoIt! resource use data collection instrument identified and measured resource use items across a range of health services in both arms including GP, nurse, physiotherapist, hospital consultants for various specialties, community psychiatric nurse, A&E and hospital inpatient stay.…”
Section: Health and Social Resource Usementioning
confidence: 99%